Student Perceptions of Humanist Literacy - Sasmita Chairuna; Uli Ramadani Siagian; Sulaiman Horta Siregar; Muhammad Asri; Muhammad Shaleh Assingkily (Journal of Contemporary Gender and Child Studies, 2024)
Literacy ability can empower and improve individual quality because of its "Multiple Effect" nature or can provide a very broad field. This article aims to analyze the perceptions of PAI students about humanist literacy. This study used a qualitative approach which was carried out using field research methods and collected data by interviews. In this study, it provides an understanding that literacy must be increased among students and cannot be abandoned because students have academic responsibilities. Therefore, to build literacy skills and awareness must be carried out systematically with effective and efficient methods. The efforts that can be made are: 1) knowing the structure and form of academic writing, 2) examining the components of PAI course material, 3) maximizing the learning process by preparing good planning.